If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3)(x + -3) + 2 = 8 Reorder the terms: 3(-3 + x)(x + -3) + 2 = 8 Reorder the terms: 3(-3 + x)(-3 + x) + 2 = 8 Multiply (-3 + x) * (-3 + x) 3(-3(-3 + x) + x(-3 + x)) + 2 = 8 3((-3 * -3 + x * -3) + x(-3 + x)) + 2 = 8 3((9 + -3x) + x(-3 + x)) + 2 = 8 3(9 + -3x + (-3 * x + x * x)) + 2 = 8 3(9 + -3x + (-3x + x2)) + 2 = 8 Combine like terms: -3x + -3x = -6x 3(9 + -6x + x2) + 2 = 8 (9 * 3 + -6x * 3 + x2 * 3) + 2 = 8 (27 + -18x + 3x2) + 2 = 8 Reorder the terms: 27 + 2 + -18x + 3x2 = 8 Combine like terms: 27 + 2 = 29 29 + -18x + 3x2 = 8 Solving 29 + -18x + 3x2 = 8 Solving for variable 'x'. Reorder the terms: 29 + -8 + -18x + 3x2 = 8 + -8 Combine like terms: 29 + -8 = 21 21 + -18x + 3x2 = 8 + -8 Combine like terms: 8 + -8 = 0 21 + -18x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(7 + -6x + x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(7 + -6x + x2)' equal to zero and attempt to solve: Simplifying 7 + -6x + x2 = 0 Solving 7 + -6x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-7' to each side of the equation. 7 + -6x + -7 + x2 = 0 + -7 Reorder the terms: 7 + -7 + -6x + x2 = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -6x + x2 = 0 + -7 -6x + x2 = 0 + -7 Combine like terms: 0 + -7 = -7 -6x + x2 = -7 The x term is -6x. Take half its coefficient (-3). Square it (9) and add it to both sides. Add '9' to each side of the equation. -6x + 9 + x2 = -7 + 9 Reorder the terms: 9 + -6x + x2 = -7 + 9 Combine like terms: -7 + 9 = 2 9 + -6x + x2 = 2 Factor a perfect square on the left side: (x + -3)(x + -3) = 2 Calculate the square root of the right side: 1.414213562 Break this problem into two subproblems by setting (x + -3) equal to 1.414213562 and -1.414213562.Subproblem 1
x + -3 = 1.414213562 Simplifying x + -3 = 1.414213562 Reorder the terms: -3 + x = 1.414213562 Solving -3 + x = 1.414213562 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 1.414213562 + 3 Combine like terms: -3 + 3 = 0 0 + x = 1.414213562 + 3 x = 1.414213562 + 3 Combine like terms: 1.414213562 + 3 = 4.414213562 x = 4.414213562 Simplifying x = 4.414213562Subproblem 2
x + -3 = -1.414213562 Simplifying x + -3 = -1.414213562 Reorder the terms: -3 + x = -1.414213562 Solving -3 + x = -1.414213562 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -1.414213562 + 3 Combine like terms: -3 + 3 = 0 0 + x = -1.414213562 + 3 x = -1.414213562 + 3 Combine like terms: -1.414213562 + 3 = 1.585786438 x = 1.585786438 Simplifying x = 1.585786438Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.414213562, 1.585786438}Solution
x = {4.414213562, 1.585786438}
| 8w^2+2w-21=0 | | 4x^3-9x^2(3)=0 | | -4.2= | | y-3=3x-6 | | m^2+3m-20= | | 4(3c-2)+5c=43 | | 15-28i=3x+(4y)i | | z*4+11=-3 | | -4y-15=21+2y | | 13x-7=11x+11 | | 3a-4=8a+6 | | S=180n-360*n | | 10n-3=57 | | 18y+11=15y+17 | | 8(h-1)=64+4+2h | | 4y=50+2d | | 7c-4=10c+14 | | 120+x=x+70 | | y-5=-.5x-(-2) | | 14+9z+4+3z-z=51 | | p^2+5p-10=0 | | 7208-220x=0. | | 5p-5=-5p-65 | | 8g-3(7g+6)= | | 2p+7whenp=2 | | 320+80x=0. | | 6z+10=3 | | 2y+7+8y-37=20 | | y-3=4x-2 | | 2.5(x+2)+4.5+1.5(x+3)=15 | | 5(n-10)=125+2n | | 15=-5-15-8u |